The next rural economies : constructing rural place in global economies (CABI, 2010)
This book underscores the extent to which different nations are confronting common challenges associated with the structural forces of globalization, while at the same time highlighting and comparing the context-specific nature of local and regional responses to rural change. Second, the book provides a comprehensive look at the emergence of place-based development. The book consists of 16 chapters presented in five parts. In the first part, five chapters raise and discuss issues concerning population change. In- and out-migration, together with in-situ demographic changes, flow from and link to the changing economies of rural and small town places. The second part of the book comprises four chapters that examine emerging economies. In each case, place-based attributes pay key roles in supporting new activities, but it is the creative action of residents, decision makers, and entrepreneurs that mobilize the opportunities. The third part of the book contains three chapters that draw out specific issues related to rural policy and governance. The three chapters that make up the fourth part of the book each directly address the issue of rural-urban relationships. In this rural-urban exchange, the opportunities and challenges of spatial relationships are explored through their impacts on place-based rural and small-town development. The final part of the book includes three chapters that explore place-based development issues in the context of renewal in resource peripheries.